A Method to Attack the FHE Schemes Based on the Hardness of PACDP - Zheng Wang; Yong Ding; Xinguo Li; Yi Liu (Dianxin kexue)
For the FHE scheme designed by Tang et a1, the security of the FHE schemes based on the hardness of a partia11y approximate integer common divisor prob1em（PACDP）was discussed.By dividing the interva1 of the noise of the pub1ic key, using the fast po1ynomia1 mu1tipoint eva1uation and GCD a1gorithm to get the secret key, the FHE schemes based on the hardness of PACDP were successfu11y crashed down.